INACTIVATION OF ASCARIS SPP. EGG IN MUNICIPAL WASTEWATER SLUDGE BOJONGSOANG BANDUNG BY LIME STABILIZATION - Muizzati Shabrina, Husna
Wastewater is resulted from domestic activity. Domestic wastewater divided into blackwater, which is from toilet, and greywater from other source besides toilet. For decreasing potential pollution risk, domestic wastewater is treated in Wastewater Treatment Plant (WWTP), either municipal domestic WWTP or sewage treatment plant. Helminth eggs in environment becomes a critical issue since WHO published new guidelines for the safe use of wastewater, excreta, and greywater in agriculture and aquaculture which expressed the equivalent limit of 1 helminth egg/gram total solid in sludge. Soil transmitted helminths, specifically Ascaris spp., are a threat for municipal WWTP sludge reuse because helminth eggs usually more environmentally persistent compared with other microorganisms. This study aims to enumerate Ascaris spp. eggs in sewage and municipal wastewater sludge, have better understanding in lime, ammonia, temperature, and contact time effect of Ascaris spp. eggs inactivation, then to find the kinetics of inactivation. Sludge and wastewater sample was taken from anaerobic, facultative, and maturation ponds of Bojongsoang WWTP, Bandung. Physical characteristics are described by measuring pH and temperature. Method for detection and enumeration use the flotation and sedimentation principal. The principal of this method is weighing 20 grams of sludge sample, added into 50 ml of detergent solution 0,1% Tween80, then sieved into 100 and 20 ?m sieve. The content on 20 ?m sieve then collected, washed, sedimented, and the supernatant discarded. Solution of ZnSO4 with specific gravity of 1.3 then added into pellets, homogenized, and the supernatant poured into 20 ?m sieve. The content was collected, washed, and the supernatant discarded. The pellets were viewed under microscope for enumerating Ascaris spp. eggs. Ascaris spp. eggs are in fertile and infertile form. The fertile form is 55 – 75 ?m long and 35 – 50 ?m wide, in golden yellow to brown color. Meanwhile the infertile form is 85 – 95 ?m long and 43 – 47 ?m wide. Inactivation process will be done in temperature 30 and 40 °C, lime concentration of 26 and 39% dry weight, and additional ammonia concentration of 1000 and 5000 mg/L.Eggs of Ascaris spp. was detected in all samples with fertile form was more abundant than infertile one with fertile percentage of 71.75 - 80%. In anaerobic, facultative, and maturation ponds a depth of 70 - 80 cm the number of eggs of Ascaris spp. fertile were 221 ± 27.15 eggs / gram, 44 ± 14.28 eggs / gram, and 55 ± 24.94 eggs / gram, respectively. As for Ascaris spp.